The moment - G., Kenny, (Kenneth Bruce Gorelick); Arista Records (New York : Arista Records, 1996)
Contains two tracks of jazz saxophone instrumental taken from The Moment album.
CD 1 : Radio Edit / (4:40) -- Album Version / (5:56).
Koleksi Khas Wiramanja.
Title from disc label.
Keywords: Jazz; Instrumental music; Saxophone music